2012
DOI: 10.1016/j.gsf.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of active tectonics in Hindu Kush: Insights from DEM derived geomorphic indices and drainage analysis

Abstract: Landscapes in tectonically active Hindu Kush (NW Pakistan and NE Afghanistan) result from a complex integration of the effects of vertical and horizontal crustal block motions as well as erosion and deposition processes. Active tectonics in this region have greatly influenced the drainage system and geomorphic expressions. The study area is a junction of three important mountain ranges (Hindu Kush-Karakorum-Himalayas) and is thus an ideal natural laboratory to investigate the relative tectonic activity resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
163
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(178 citation statements)
references
References 28 publications
1
163
0
14
Order By: Relevance
“…Convex hypsometric curves are typical of a youthful stage; S-shaped curves are related to a maturity stage, and concave curves are indicative of a peneplain stage (Strahler, 1957;Gardner et al, 1990;Delcaillau et al, 1998;Keller and Pinter., 2002; (Figure 3). Strahler, 1952;Pérez-Peña et al, 2009;Mahmood and Gloaguen, 2012) A simple way to characterize the shape of the hypsometric curve for a given drainage basin is to calculate its hypsometric integral (HI). The integral is defined as the area under the hypsometric curve and can be calculated (Keller and Pinter, 2002):…”
Section: Hypsometric Curve and Hypsometric Integralmentioning
confidence: 99%
See 1 more Smart Citation
“…Convex hypsometric curves are typical of a youthful stage; S-shaped curves are related to a maturity stage, and concave curves are indicative of a peneplain stage (Strahler, 1957;Gardner et al, 1990;Delcaillau et al, 1998;Keller and Pinter., 2002; (Figure 3). Strahler, 1952;Pérez-Peña et al, 2009;Mahmood and Gloaguen, 2012) A simple way to characterize the shape of the hypsometric curve for a given drainage basin is to calculate its hypsometric integral (HI). The integral is defined as the area under the hypsometric curve and can be calculated (Keller and Pinter, 2002):…”
Section: Hypsometric Curve and Hypsometric Integralmentioning
confidence: 99%
“…The HC index is one of the geomorphic indices that has been considered as a powerful tool for quantifying the topographic features and differentiate zones deformed by active tectonics (Keller and Pinter, 2002;Chel et al, 2003;Pérez-Peña et al, 2009;Pedrera et al, 2009;Mahmood and Gloaguen, 2012). However, in Vietnam, this is the first time the method is adopted for the assessment of the active tectonics in the Lo River fault zone and the Tam Dao area (Ngo et al, 2016), but statistical moments of the hypsometric curve has not been analyzed and assessed.…”
Section: Introduction *mentioning
confidence: 99%
“…The occurrence of a debris flow is mostly influenced by local topographical characteristics, active tectonics and rainfall (Maroukian et al, 2008). Although mainly controlled by tectonics (Mahmood and Gloaguen, 2012), the former two factors can provide the basis for occurrence of debris flows (Wadge, 1994;Anbalagan and Singh, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These researchers concluded that relatively high potentials of active tectonics are associated with the indicative values of the IRAT. Mahmood and Gloaguen (2012) used seven geomorphic indices to compute the IRAT using GIS at the Hindu Kush, Karakorum, and Himalayas ranges. The indicative values of the IRAT are consistent with known uplift rates, landform characteristics and geology.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been proposed to extract river profiles and channel parameters from DEM. For example, Snyder et al [19] and Kirby and Whipple [21] have developed a group of built-in functions in ARC/INFO to create flow accumulation arrays and delineate drainage basins; Mahmood and Gloaguen [26] calculated the indices of relative active tectonics (IRAT) in the Geography Information System (GIS) from a DEM in Hindu Kush region. In addition, scientific programming languages such as Matlab and SAS scripts were integrated in GIS to color-code stream profiles by their steepness and concavity indices: Shahzad et al [22] have developed the package TecDEM using MATLAB for drainage network partition and river profile analysis from DEM and this package was also used by Vezzoli et al [27] to extract the fluvial network in Western Greater Caucasus.…”
Section: Introductionmentioning
confidence: 99%